2022
DOI: 10.1021/acschemneuro.1c00656
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Parkinson’s Disease Activity of Sanghuangprous vaninii Extracts in the MPTP-Induced Zebrafish Model

Abstract: Parkinson’s disease (PD) is a devastating disease of the central nervous system that occurs mainly in the elderly age group, affecting their quality of life. The PD pathogenesis is not yet fully understood and lacks the disease-modifying treatment strategies. Sanghuangprous vaninii (S. vaninii) is a perennial fungus with a plethora of pharmacological activities including anti-cancer and antioxidant activity and so on. However, no study till date has reported its neuroprotective effect against symptoms that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…To evaluate the neuroprotective effect of active peptides on Parkinson's disease, the PD models of zebrafish were established using MPTP at concentrations of 70 μM and incubated for 72 h, respectively. 32 In addition, we detected the loss of DA neurons and blood vessels using transgenic zebrafish vmat2:GFP and fli1:GFP . Results showed that the DA neuron length of MPTP-treated zebrafish decreased significantly compared with the control.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the neuroprotective effect of active peptides on Parkinson's disease, the PD models of zebrafish were established using MPTP at concentrations of 70 μM and incubated for 72 h, respectively. 32 In addition, we detected the loss of DA neurons and blood vessels using transgenic zebrafish vmat2:GFP and fli1:GFP . Results showed that the DA neuron length of MPTP-treated zebrafish decreased significantly compared with the control.…”
Section: Resultsmentioning
confidence: 99%
“…In this scenario, there is emerging evidence on the neuroprotective activity of different phenolic compounds present in various plant sources regarding inhibition of acetylcholinesterase (AchE), Aβ aggregation, proinflammatory markers, and 1-methyl-4phenyl-1-1,2,3,6-tetrahydropyridine (MPTP)-induced apoptosis, among others [12]. Thus, phenolic compounds from different matrices have been shown to have neuroprotective capacity, such as Eucommia ulmoides Oliver (rich in phenolic acids, flavonoids, and iridoid glycosides), herbaceous peony (with paeoninflorin as the main active ingredient), and Sanghuangprous vaninii (an extract rich in caffeic acid); they may ameliorate the dopaminergic deficiency in the MPTP-induced model in the zebrafish brain [12][13][14]. However, common phenolics present in different sources, for example, quercetin, which is contained in different matrices such as apple, chocolate, or cherry [15], have been shown to have both antioxidant and tyrosinase inhibitory actions [16].…”
Section: Introductionmentioning
confidence: 99%
“…Given the structural similarities between the zebrafish dopamine neuron system and the human striatum, zebrafish has become an excellent model for neurodegenerative and neuropharmacological studies 15,16 . Some studies applied the MPTP‐induced zebrafish PD model to characterize PD‐like cognitive deficits by assessing spatial working memory and spontaneous alternation behavior 17,18 . MPTP‐induced zebrafish PD model is used to study the mitochondria function in the berberine's neuroprotective activity 19 .…”
Section: Introductionmentioning
confidence: 99%